Surveillance ecological study of cellular responsesin three marine edible bivalve species to Cd present in their marine habitat,Mediterranean sea in Alexandria, Egypt. - Radwan, Eman Hashem (JOURNAL OF ADVANCES IN BIOLOGY, 2014)
Coastal habitats experience large fluctuations of environmental factors such as salinity; they also serve as the natural sinks for trace metals. Bivalves are exposed to the elevated concentrations of metals in water that can strongly have an effect on their histology. The present work includes a list of three edible bivalve species collected from marine water;Mediterranean sea in Alexandria, Egypt. All the identified species are included in class bivalvia. The present study aims to evaluate the environmental salinity and cadmium during two years 2011-2013 of two locations;easern harbor and el asafra ,Aleaxandria,Egypt of the Mediterranean coast to investigate their effect on the histology of three main edible bivalve species.From each station, fifteen bivalve (clams, date mussels and oysters) were collected monthly.